Direct measurement of Ni incorporation into Fe3O4(001). Issue 24 (8th June 2018) - Ryan, P. T. P.; Jakub, Z.; Balajka, J.; Hulva, J.; Meier, M.; Küchle, J. T.; Blowey, P. J.; Thakur, P. Kumar; Franchini, C.; Payne, D. J.; Woodruff, D. P.; Rochford, L. A.; et al.
Abstract : The normal incidence X-ray standing wave (NIXSW) technique has been used to follow the evolution of the adsorption geometry of Ni adatoms on the Fe3 O4 (001)-(√2 × √2) R 45° surface as a function of temperature. Abstract : The normal incidence X-ray standing wave (NIXSW) technique has been used to follow the evolution of the adsorption geometry of Ni adatoms on the Fe3 O4 (001)-(√2 × √2) R 45° surface as a function of temperature. Two primary surface region sites are identified: a bulk-continuation tetrahedral site and a sub-surface octahedral site, the latter site being preferred at higher annealing temperatures. The ease of incorporation is linked to the presence of subsurface cation vacancies in the (√2 × √2) R 45° reconstruction and is consistent with the preference for octahedral coordination observed in the spinel compound NiFe2 O4 .